1999
DOI: 10.1111/j.1469-7793.1999.0507p.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic modulation of hyperpolarization‐activated current in acutely isolated rat dorsal root ganglion neurons

Abstract: The hyperpolarization-activated cation current (IH) is expressed differentially in various subpopulations of rat sensory neurons. For example, IH is infrequently expressed by C-and Aä-type dorsal root ganglion (DRG) neurons but is prominent in most Aá-and Aâ-type DRG neurons (Harper & Lawson, 1985a,b;Scroggs et al. 1994; Valiere & McLachlan, 1996). Since C-and Aä-type DRG neurons are typically involved in the transmission of different types of information than Aâ-and Aá-type DRG neurons, it is likely that ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 44 publications
12
90
1
Order By: Relevance
“…In addition, T-rich cells, like most other small T-type channelcontaining DRG cells, are responsive to capsaicin (Cardenas et al, 1995;Todorovic et al, 2001) and show a hyperpolarizing response to 5-HT. In contrast, medium DRG cells with prominent T-type currents and ADPs are unresponsive to capsaicin (Cardenas et al, 1995), show depolarizing responses to 5-HT (Cardenas et al, 1999), and express a high density of HVA currents (Scroggs and Fox, 1992;Cardenas et al, 1995;Dubreuil et al, 2004). These findings also support our assertion that T-rich cells are a distinct and unique subpopulation of DRG neurons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, T-rich cells, like most other small T-type channelcontaining DRG cells, are responsive to capsaicin (Cardenas et al, 1995;Todorovic et al, 2001) and show a hyperpolarizing response to 5-HT. In contrast, medium DRG cells with prominent T-type currents and ADPs are unresponsive to capsaicin (Cardenas et al, 1995), show depolarizing responses to 5-HT (Cardenas et al, 1999), and express a high density of HVA currents (Scroggs and Fox, 1992;Cardenas et al, 1995;Dubreuil et al, 2004). These findings also support our assertion that T-rich cells are a distinct and unique subpopulation of DRG neurons.…”
Section: Discussionsupporting
confidence: 80%
“…In larger, faster-conducting A␣-and A␤-cells, 5-HT almost exclusively elicits depolarizing effects on membrane potential (Todorovic and Anderson, 1992;Cardenas et al, 1999). In contrast, experiments using intact DRG-sciatic nerve preparations have shown that in smaller, slower-conducting A␦-and C-cells, 5-HT preferentially elicits hyperpolarizing effects on membrane potential (Todorovic and Anderson, 1992).…”
Section: T-rich Cells Display Nociceptive Characteristicsmentioning
confidence: 89%
“…There was no significant reduction in current amplitude in the presence of TTX. This is in agreement with previous studies showing that rat DRG neurons that express a prominent I A also express only TTX-resistant Na ϩ currents (Cardenas et al, 1999(Cardenas et al, , 2001). The peak current value at multiple potentials was recorded to generate I-V curves (Fig.…”
Section: Characterization Of Ttx-resistant Nasupporting
confidence: 82%
“…The threshold for I h activation ranged between -55 and -60 mV; voltage for half-maximal activation and the slope coefficient were V 1/2 ϭ Ϫ73.2 Ϯ 0.8 mV and k ϭ 8.5 Ϯ 0.7 mV, respectively, which was similar to values reported by Cardenas et al (1999) (V 1/2 ϭ Ϫ73.3 mV, k ϭ 7.0 mV).…”
Section: Hcn Channels Protein and Functional Expressionsupporting
confidence: 76%
“…On the functional level, I h kinetics and pharmacology were close to those reported previously (Cardenas et al 1999;Scroggs et al 1994;Yagi and Sumino 1998). The threshold for I h activation ranged between -55 and -60 mV; voltage for half-maximal activation and the slope coefficient were V 1/2 ϭ Ϫ73.2 Ϯ 0.8 mV and k ϭ 8.5 Ϯ 0.7 mV, respectively, which was similar to values reported by Cardenas et al (1999) (V 1/2 ϭ Ϫ73.3 mV, k ϭ 7.0 mV).…”
Section: Hcn Channels Protein and Functional Expressionsupporting
confidence: 68%